2017
DOI: 10.1186/s41205-017-0012-5
|View full text |Cite
|
Sign up to set email alerts
|

Medical 3D printing: methods to standardize terminology and report trends

Abstract: BackgroundMedical 3D printing is expanding exponentially, with tremendous potential yet to be realized in nearly all facets of medicine. Unfortunately, multiple informal subdomain-specific isolated terminological ‘silos’ where disparate terminology is used for similar concepts are also arising as rapidly. It is imperative to formalize the foundational terminology at this early stage to facilitate future knowledge integration, collaborative research, and appropriate reimbursement. The purpose of this work is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 12 publications
0
25
0
1
Order By: Relevance
“…Following acquisition the DICOM datasets must be transferred to the 3D printing software from the clinical machine. For 3D printing to become an efficient clinical service, an institutional process for transferring the data from the scanners must be created and linked to an order within the electronic medical record [1]. One solution is to create a terminal that each scanner may send 3D printing data to or may be used to pull the data from the clinical storage system.…”
Section: Import Imaging To 3d Printing Softwarementioning
confidence: 99%
“…Following acquisition the DICOM datasets must be transferred to the 3D printing software from the clinical machine. For 3D printing to become an efficient clinical service, an institutional process for transferring the data from the scanners must be created and linked to an order within the electronic medical record [1]. One solution is to create a terminal that each scanner may send 3D printing data to or may be used to pull the data from the clinical storage system.…”
Section: Import Imaging To 3d Printing Softwarementioning
confidence: 99%
“…The first of the AM applications in the medical sector was the use of computerised tomography to create images of subjects from any angle. In addition, AM has been applied in different categories of medical applications, such as for surgical and diagnostic aids, prosthesis development, and manufacturing related to medicine and tissue engineering (Chepelev et al, 2017;Tofail et al, 2018).…”
Section: Additive Manufacturingmentioning
confidence: 99%
“…For 3D printing to become a reimbursable service provided by radiologists, it is prudent to develop a standardized lexicon on naming models, the process of printing itself, and other related factors. Chepelev et al (118) conducted a literature search in order to standardize terminology related to 3D printing. They concluded that "3D printing", "additive manufacturing", and "rapid prototyping" are three nearly synonymous terms used to describe the concept of 3D printing.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that "3D printing", "additive manufacturing", and "rapid prototyping" are three nearly synonymous terms used to describe the concept of 3D printing. They found that by 2015, "3D printing" was the most frequent descriptor (>60%) and they advocate its use over the other two terms (118). …”
Section: Introductionmentioning
confidence: 99%